Nicaragua : Pension Reform Proposal - World Bank (2013)
The study reviews the current social security system, and its characteristics, analyzing the shortcomings of the Old Age, Disability and Survivor's Insurance (IVM) system, based on a defined benefit Pay-as-you-go (PAYG) scheme, no longer viable, given its low payroll taxes, overly generous benefits, and high rates of evasion, all systemic problems, which combined with institutional, and administrative weaknesses of the Instituto Nicaraguense de Seguridad Social (INSS), caused a cash deficit since 1997, and depletion of its reserves for the immediate future. The report explores long term finances, and the rationale for undertaking a systemic reform with mandatory, and defined contributions, based on individual capitalization accounts. It recommends closing the current PAYG system to new entrants, with the proviso for those aged 45-50, to opt for the new system, granting recognition for their acquired rights. General revenues, payroll taxes, and pension fund reserves, or other possible sources, should finance the transition to the new scheme, to be administered by pension fund managers. Funds should be invested both domestically, and abroad, ensuring diversification of the portfolio, as well as protection from local economic, and political manipulation.